Mindfulness arrives at work: Deepening our understanding of mindfulness in organizations - REB, Jochen (Institutional Knowledge at Singapore Management University, 2020)
Mindfulness has become an increasingly popular practice and in parallel scholarly research has grown considerably. However, the study of mindfulness at work remains limited and motivates this special issue on “Mindfulness at Work: Pushing Theoretical and Empirical Boundaries.” In this introduction to the special issue we offer a brief initial grounding in the literature on mindfulness at work and in organizations. We then turn attention to how the six articles in this special issue advance this nascent field. We use both as a point of departure for considering the benefits and limits of mindfulness in organizations as well as the contextual (e.g., leadership) moderators and boundary conditions on mindfulness. We also detail the emerging evidence on both the general cognitive and workplace-specific mechanisms through which mindfulness operates. We offer directions for future research that highlight both the interplay of individual mindfulness and interpersonal relations and organizing, as well as means of increasing mindfulness beyond traditional meditative practice. Finally, we conclude with a brief outlook to a promising future ahead for this growing field that we believe has the potential to substantially reduce suffering and increase flourishing at workplaces throughout the world.